Migrações internacionais: um estudo sobre trabalhadores imigrantes em Francisco Beltrão-PR (2009-2020) - Pereira , Fagner Guglielmi (2022)
This thesis is the result of a study on immigrant workers who resided in Francisco Beltrão-PR between 2009 and 2020. They are part of contemporary international migrations, originating in countries such as Bangladesh, Ghana, Senegal and Somali. Therefore, we seek to identify in this search: i) life trajectories in the place of origin; ii) process of moving from the place of origin to the place of destination; iii) labor engagement and work relationships at the destination(s) and iv) emerging ways of life of migrant populations is towns in the country cities of Paraná state, such Francisco Beltrão-PR as a reference, where the empirical work was carried out. With the intention of contributing to the studies of international migrations, we started from the experiences of immigrants in what could offer material to examine the as a historical as social phenomenon. In this sense, it was intended to highlight the ways of life and work Africans and Asians before and after migration. We also seek to point out social manifestations, work relationships and power when taking personal experiences: senses, meanings and feelings, relationships and problems shared by immigrants.